Pengembangan Pendidikan Berbasis Pesantren: (Kajian Kurikulum Ideal Di Pesantren Dalam Era Globalisasi) - Asykuri, Moh. (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2014)
Development of education in boarding school in responding to the changing era at least there are things that need to be maintained and should not change the basic values of pesantren (sincerity, simplicity, independence, ukhuwah islamiyah, free spirit, community, struggle and sacrifice). But on the other hand there is also a need for more urgent development beyond that, which among others concerning building and revitalizing the ideal curriculum in the pesantren.